2003
DOI: 10.1292/jvms.65.157
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Analysis of Hepatic Lymphocytes from Healthy Dogs

Abstract: ABSTRACT. Phenotypes of lymphocytes from laparoscopically biopsied liver tissues of eleven healthy beagle dogs were analyzed. CD21-lymphocytes (non-T non-B lymphocytes), and the CD4 + /CD8 + ratio in the canine hepatic lymphocytes were 54.8 ± 11.9%, 4.7 ± 3.1%, 40.7 ± 13.2%, and 0.33 ± 0.12, respectively, while those in peripheral blood lymphocytes were 85.4 ± 6.5%, 9.3 ± 6.1%, 5.3 ± 1.8%, and 1.64 ± 0.36, respectively. These results indicated that the constitution of hepatic lymphocytes quite differed from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
1
4
2
Order By: Relevance
“…of different sample collection methods. 24,25 For example, investigators in 1 study 24 reported a mean ratio of CD3-positive-to-CD21-positive cells of 2.1 in spleen samples from 3 healthy Beagles, whereas the mean T:B identified in spleen samples of 5 healthy Beagles in the present study was 2.3.…”
Section: Investigated Mononuclear Cells In the Spleen Of Dogs Infecte...contrasting
confidence: 44%
See 2 more Smart Citations
“…of different sample collection methods. 24,25 For example, investigators in 1 study 24 reported a mean ratio of CD3-positive-to-CD21-positive cells of 2.1 in spleen samples from 3 healthy Beagles, whereas the mean T:B identified in spleen samples of 5 healthy Beagles in the present study was 2.3.…”
Section: Investigated Mononuclear Cells In the Spleen Of Dogs Infecte...contrasting
confidence: 44%
“…Some flow cytometry-based studies have focused on lymphocyte development in lymphatic organs (including the spleen) 24 or the characterization of lymphocytes found in the liver in healthy dogs. 25 In an earlier study, 29 investigators analyzed T-cell subsets in lymph nodes, spleen, bone marrow, thymus, and blood of healthy dogs by use of monoclonal antibodies. Another flow cytometry-based study 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our dog, there were large numbers of CD3+ lymphocytes within the liver tissue. CD8+ lymphocytes are found to be more numerous than CD4+ lymphocytes in the liver of healthy dogs [4]. However, hepatic CD4+ lymphocytes were predominant in this case.…”
contrasting
confidence: 51%
“…Cryostat sections (8 µm in thick) were prepared and stained by the avidin-biotin-peroxidase complex method with an antibody against human CD3 (CD3-12; Serotec, Oxford, UK). Furthermore, hepatic and peripheral lymphocytes were analyzed using anti-canine CD3 fluorescein isocyanate conjugated (-FITC) antibody (CA17.2A12; Serotec), antihuman CD21 phycoerythrin conjugated (-PE) antibody (Bly4; Becton-Dickinson, Franklin Lakes, NJ), anti-canine CD4-FITC antibody (YKIX302.9; Serotec), and anti-canine CD8α-PE antibody (YCATE55.9; Serotec) by flow cytometric method as described by Sakai et al [4]. Phenotypes were identified on the basis of the lymphocytes of 5,000 events obtained by gating on the screen for the forward scatter versus side scatter dot plot of a FACS Calibur (BectonDickinson).…”
mentioning
confidence: 99%